PTU-008 Is cranial to caudal approach a feasible technique for complete mesocolic excision (cme) in laparoscopic transverse colectomy?. (22nd June 2015) - Shimada, T; Tsuruta, M; Hasegawa, H; Okabayashi, K; Kondo, T; Matsuda, M; Yahagi, M; Yoshikawa, Y; Kitagawa, Y
Abstract : Introduction: Laparoscopic transverse colectomy (LTC) is one of the most challenging techniques because the region of its mesentery and lymph node (LN) dissection is controversial. In addition, anatomical anomalies are often observed in the root of middle colic artery (MCA), which is surrounded by critical vessels such as superior mesenteric vein (SMV), splenic vein (SPV) and inferior mesenteric vein (IMV). We believe that cranial to caudal approach is one of the answers against how to overcome the hurdle of CME and LN dissection in LTC because it's relatively easy to discern the border of transverse colon mesentery from pancreas. Another is to clarify the dominantly feeding vessel and establish the interest region of lymphandectomy by using CT colonography and angiography preoperatively. Method: First, we open the bursa omentalis widely through the gastrocolic ligament, and subsequently mobilise and take down the hepatic and splenic flexure. The anterior lobe of transverse mesocolon is then dissected at the inferior border of the pancreas with the so-called cranial to caudal approach. Right gastroepiploic vein (RGEV) is a landmark to reach SMV. Exposing pancreatic head and second potion of duodenum and blunt dissection are also important to take down hepatic flexure of transverse colon and detach mesentery of transverse colon. In the process, we transect one or two accessory right colonic vein (ARCV). With skeletonizing SMV to proximal side, merging of SMV, SPV and IMV are uncovered. We think it's critical to harvest the lymph nodes completely in the region enclosed by SMV, SPV and IMV where there should be generally the root of MCA. CT angiography is a robust support to comprehensively recognise the vessel anatomical anomalies and dissected region of colon mesentery. Continuously, it's possible to dissect the root of ileocolic and right colic vessels with skeletonizing ventral surface of SMA and SMV in this approach. Results: We herein present our practical laparoscopic transverse colectomy with LN dissection in video as attatched to demonstrate our concept and strategy in this field. Conclusion: We think that cranial to caudal approach is a feasible technique for complete mesocolic excision in laparoscopic transverse colectomy. Disclosure of interest: None Declared.